Proceedings of the ACM/IEEE Joint Conference on Digital Libraries in 2020 2020
DOI: 10.1145/3383583.3398514
|View full text |Cite
|
Sign up to set email alerts
|

Towards Knowledge Maintenance in Scientific Digital Libraries with the Keystone Framework

Abstract: Scientific digital libraries speed dissemination of scientific publications, but also the propagation of invalid or unreliable knowledge. Although many papers with known validity problems are highly cited, no auditing process is currently available to determine whether a citing paper's findings fundamentally depend on invalid or unreliable knowledge. To address this, we introduce a new framework, the keystone framework, designed to identify when and how citing unreliable findings impacts a paper, using argumen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Parties responsible for the retraction, including authors for self-retraction and investigative committees for misconduct-related retraction, should search citation databases and notify citing authors directly to the retraction notice, for follow-up action (such as corrections, retrenchment in new citations, etc.). This is particularly important for papers whose conclusions fundamentally depend on retracted work (Fu and Schneider 2020). While currently no tools provide notification to the authors of pre-retraction citations, such tools could also be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Parties responsible for the retraction, including authors for self-retraction and investigative committees for misconduct-related retraction, should search citation databases and notify citing authors directly to the retraction notice, for follow-up action (such as corrections, retrenchment in new citations, etc.). This is particularly important for papers whose conclusions fundamentally depend on retracted work (Fu and Schneider 2020). While currently no tools provide notification to the authors of pre-retraction citations, such tools could also be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, we may integrate tests like the CRAAP test [5] or automated heuristics, e.g., scientific publications before websites, highly influential over low cited publications, etc. Note that we are aware of highly influential papers that have been retracted but handling such cases in digital libraries is a research field on its own [11]. But if we do not have curated information available, we must think about alternatives here.…”
Section: Concluding Discussion On Narrative Plausibilitymentioning
confidence: 99%
“…Another common recommendation has been to remove retracted papers entirely (e.g., [22,36,42,43]); for instance, Rzymski suggests "hard retraction" to handle "cases of fraud or grave errors with broad impacts, " as a mechanism for removing articles from the publisher site and most indexes, except for a limited access repository dedicated to retracted papers [43]. Alerting authors who previously cited newly retracted work has also been suggested [44,45].…”
Section: Cope Icmjementioning
confidence: 99%
“…The need for retraction can be raised at any time after publication, and this time has been as long as 45 years (e.g., [116]). From the point of view of citation and use, there are two interrelated issues: First, the longer a publication is "alive" in the literature before retraction, the more time it has had to accrue citation and use while considered normal citable literature; this increases the potential impact on the rest of the literature, because there is currently no systematic process for updating knowledge claims when publications have already been cited by the time they are retracted [45]. Second, publications with shorter time to retraction may also receive fewer post-retraction citations [24].…”
Section: Develop Best Practices For Coordinating the Retraction Proce...mentioning
confidence: 99%